Dilute acid hydrolysis pretreatment for sugar and organic acid production from pineapple residues - K. K., Ariffin; N., Masngut; Mazrul Nizam, Abu Seman; Syed Mohd Saufi, Tuan Chik; Shariza, Jamek; Mohd Shafiq, Mohd Sueb (IOP Publishing, 2020)
Pineapple residue which is pineapple leaves composed of about 80% of carbohydrate containing lignin, cellulose and hemicellulose was utilised for the production of fermentable sugars. However, pretreatment of lignocellulosic material is required to remove hemicellulose and lignin and reducing crystallinity of cellulose to enhance hydrolysis. This paper presents an experimental study of acid hydrolysis pretreatment in pineapple residue to produce sugar and organic acid using sulphuric acid. The effect of different acid concentration (4%, 8% and 12% v/v), solid-to-liquid ratio (10%, 15% and 20% w/v) and reaction time (40, 80, and 120 minutes) of acid hydrolysis pretreatment on pineapple residue at temperature of 100°C were studied to produce high yield of sugar and low organic acid production. As a result, the highest of sugar concentration simultaneously with the lowest of organic acids concentration from pineapple residue were 2.68 ± 0.12 g/L (xylose), 8.84 ± 0.11 g/L (glucose), 1.62 ± 0.20 g/L (formic acid) and 3.28 ± 0.26 g/L (acetic acid); recorded at conditions of 12% acid concentration (v/v), 20% solid-to-liquid ratio and 80 minutes of reaction time. In conclusion, dilute acid hydrolysis pretreatment was a great approach in order to produce high sugar at the same time with low organic acids yield from pineapple residue at mild conditions.